Rhizospheric Bacillus spp. as biocontrol agents against maize downy mildew and growth promoters - Mugiastuti, Endang; Manan, Abdul; Soesanto, Loekas; Primayuri, Deviana; Sundari, Dini (Jurnal AGRO, 2025)
Downy mildew is one of the major patogen limiting maize productivity in Indonesia. Effective mitigation strategies are essential due to the significant yield losses it causes. Biological control is an environmentally viable alternative method of disease management. Bacillus spp. are biological control agent capable of producing metabolic chemicals that can inhibit plant infections, hence holding potential for downy mildew management. This study aimed to evaluate the effectiveness of Bacillus spp. from the maize rhizosphere to manage downy mildew and promote maize plant growth. The research employed a completely randomized block design, consisting of four treatments and six replications. The treatments comprised Bacillus amyloliquefaciens BB.R3, B. subtilis BK.R5, Bacillus spp. BK.R9, fungicides treatment (metalaxyl), and control group for comparison. The observed variables included spore germination, incubation period, disease incidence, disease severity, Area Under Disease Progression Curve (AUDPC), number of leaves, plant height, fresh shoot weight, and fresh root weight. The findings revealed that B. amyloliquefaciens BB.R3, B. subtilis BK.R5, and Bacillus spp. BK.R9 effectively inhibited downy mildew by decreasing spore germination by 80.55-100%, prolonging the incubation period, and inhibiting disease incidence by 20.37-53.70%, disease severity by 25.64-62.56%, and AUDPC by 22.21-63.37%. B. amyloliquefaciens BB.R3 can enhance plant growth by augmenting root weight by 122.63% and maize plant weight by 80.26%.   ABSTRAK   Penyakit bulai merupakan salah satu penyakit utama yang menghambat produksi jagung di Indonesia. Upaya pengelolaan penyakit bulai perlu dilakukan mengingat besarnya kehilangan yang ditimbulkan.  Pengendalian hayati merupakan salah satu alternatif pengendalian yang ramah lingkungan dan berkelanjutan. Bacillus spp. adalah bakteri yang mampu menghasilkan senyawa metabolik, dapat mengendalikan pathogen tanaman sehingga berpotensi sebagai pengendali penyakit bulai.  Penelitian ini bertujuan untuk mengetahui kemampuan Bacillus spp. asal rizosfer untuk mengendalikan penyakit bulai dan mengoptimalkan pertumbuhan tanaman jagung. Penelitian menggunakan Rancangan Acak Kelompok Lengkap, dengan 4 perlakuan dan 6 ulangan. Perlakuan meliputi Bacillus amyloliquefaciens BB.R3, Bacillus subtilis BK.R5, Bacillus spp.. BK.R9, serta fungisida (metalaksil) dan kontrol sebagai pembanding. Variabel yang diamati meliputi perkecambahan spora, masa inkubasi, kejadian penyakit, intensitas penyakit, AUDPC, jumlah daun, tinggi tanaman, bobot tanaman segar, dan bobot akar segar. Hasil penelitian menunjukkan B. amyloliquefaciens BB.R3, B. subtilis BK.R5, Bacillus spp.. BK.R9 mampu menekan penyakit bulai jagung, dengan menurunkan perkecambahan spora 80,55-100 %, menunda masa inkubasi, menurunkan kejadian penyakit sebesar 20,37-53,70 %, intensitas penyakit sebesar 25,64-62,56%, dan AUDPC sebesar 22,21-63,37%. B. amyloliquefaciens BB.R3 dapat memacu pertumbuhan tanaman, dengan meningkatkan bobot akar sebesar 122,63 % dan bobot tanaman jagung sebesar 80,26%.   Kata kunci: Bacillus, jagung, pengendalian hayati,  Peronosclerospora maydis, ramah lingkungan